A lightweight two-gateway based payment protocol ensuring accountability and unlinkable anonymity with dynamic identity. (January 2017) - Sureshkumar, Venkatasamy; Anitha, R.; Rajamanickam, N.; Amin, Ruhul
Highlights: A robust payment protocol is proposed to make payment using two cards of different banks. The protocol is lightweight so that it could be utilized in portable devices. The protocol has been analysed for accountability, untraceability and unlinkability properties using the formal method strand space model with the automated tool CPSA. Comparative analysis of the protocol for security features and number of cryptographic operations with state-of-the-art reveals that the proposed protocol outperforms the existing schemes. Graphical abstract: Abstract: In the current scenario, mobile web payment provides a standard platform to the Internet users for online digital goods shopping. Though the majority of online transactions use single gateway, there is a need for multi-gateway, due to insufficient balance in a customer's account in a specific bank. There are a few payment protocols which support a transaction using multiple cards, but they too have some limitations like cards should be of the same bank and the process should be based on independent transactions. This paper proposes an efficient payment protocol that is used for making online transactions via two gateways for purchasing digital goods to overcome the above mentioned limitations. The proposed protocol is simulated using the automated tool Cryptographic Protocol Shape Analyzer (CPSA) and it satisfies accountability, anonymity and atomicity properties. Formal proof of correctness is provided using the strand space model. The protocol is then compared with the state-of-the-art protocols in terms of different security features and computational overhead. Results show that our protocol achieves better performance than other protocols.